An inquiry into relationships between certain personality factors and attitudes to mathematics in some selected schools in the range standards three to five - Light, David Leon (Rhodes University, Faculty of Education, Department of Education, 1984)
Mathematics--Study and teaching (Elementary)--Psychological aspects
Keywords: Uncatalogued